Ilmastonmuutos pääkaupunkiseudulla - Mäkelä, Antti; Lehtonen, Ilari; Ruosteenoja, Kimmo; Jylhä, Kirsti; Tuomenvirta, Heikki; Drebs, Achim (Raportteja / Ilmatieteen laitos, ISSN 0782-6079, 2016)
Klimatförändringen i huvudstadsregionen.
Keywords: ilmastonmuutokset; vaikutukset; ilmasto; säähavainnot; ilmastomallit; pääkaupunkiseutu (Suomi); skenaariot; klimatförändringar; effekter; klimat; väderobservationer; klimatmodeller; huvudstadsregionen (Finland); Helsinki; Espoo; Vantaa; Kauniainen; Helsingfors; Esbo; Vanda; Grankulla